A Religious Interest Questionnaire for use with psychiatric patients - Littlewood, Roland (Mental health, religion & culture, 1998)
The renewed research on religious experience and psychiatric Ulness requires a short and accessible measure of religious background, experience, belief and practice among patients and their families. The fourth edition of an unpublished questionnaire, previously used in clinical practice and research, is presented along with its scoring notes and its limitations.